Temperament profiles to differentiate between stress-resilient and stress-affected children during Covid-19 pandemic - Scaini, Simona; Caputi, Marcella; Giani, Ludovica; Forresi, Barbara (Psychology Hub, 2022)
Covid-19 pandemic has posed unprecedented challenges to individual resilience, especially among children who are the most affected by its psychological consequences. We aim to investigate temperament profiles that might constitute a potential risk factor for the development of psychopathology and low levels of resilience in children experiencing Covid-19 quarantine. The sample included 158 Italian children aged 5 to 10 years (48% boys, M = 7.4, SD = 1.8) recruited through a snowball sampling from the general population. Temperament, psychopathological symptoms, and resilience were assessed with the Junior Temperament and Character Inventory, the Strengths and Difficulties Questionnaire, and the Child and Youth Resilience Measure. Profile Analysis was employed to outline temperament differences between stress-resilient and stress-affected children. Results evidenced that resilient children displayed high levels of persistence and reward dependence, and low levels of novelty seeking. Behavioral difficulties were associated with low levels of persistence and reward dependence, and high levels of novelty seeking. Internalizing symptoms were more likely among children with high harm avoidance and low persistence. These findings underscore the importance of examining different temperament dimensions and their associations, especially when profiling phenotypes in trying to identify the links among temperament, vulnerability to psychopathology and resilience during stressful periods.